THE EXPERIENCE AND MANAGEMENT OF - Hendey, Louise (My University, 2011)
Business people face ongoing challenges in managing their family and work demands; while organisations assume that their employees will contribute significantly to organisational goals by managing these demands. Organisations have been slow to progress to meet the needs of their employees who have adapted roles, beliefs and actions to accommodate a work-family balance. This research explores the experience and management of the workfamily balance in South Africa. By employing 4 focus groups in a sample of 36 participants, the research sought to explore the personal, family and work experiences of business people in South Africa within the context of the work-family balance. It further aimed to provide suggestive evidence of the differences between men and women in their experiences of work-family balance; and to offer insights to organisations based on these multiple experiences. The investigation was descriptive in nature as it allowed participants to share their stories to derive the research data. A combination of content and conversational analysis was utilised to collate the data. The main findings of the research suggest that work-family roles have a significant effect on individuals who experience time pressures, stress and personal crisis juxtaposed with emotions of fulfilment. It provides evidence of the complex experiences in the family unit as a result of these multiple roles including effects on family functioning, increased marital conflict and lifestyle. This study illustrates how individuals employ skills acquired through work to facilitate solutions in the family environment and vice-versa. It also indicates the importance of balanced leaders and business action to create an organisational culture supporting work-family balance. It suggests differences between men and women in what they believe and how they respond to work-family balance. Primarily however, this research suggests that a significant portion of the experiences hinge on intrinsic factors such as emotional intelligence, beliefs and personality that underpin personal choices to facilitate work-family balance
MBA - WBS
Keywords: Work-life balance